Pengaruh Model Problem Based Learning (PBL) Berbantuan Aplikasi Desmos terhadap Kemampuan Literasi Matematis Siswa MAS Alwashliyah 12 Perbuangan - Mariani, Sri; Simamora, Yumira; Rizqi, Nur Rahmi (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This research aimed at (1) finding out whether there is an effect of Problem Based Learning (PBL) assisted by the desmos application on the mathematical literacy skills of MAS Al Washliyah 12 Perbaungan students (2) finding out the effectiveness of using the desmos application in quadratic function materials on the mathematical literacy skills of MAS Al Washliyah 12 students. This is a mix method with factorial experiment design. The population is all students of class X MAS Al Washliyah 12 Perbaungan academic year 2022/2023. The sample is determined by Simple Random Sampling. The data collection technique in this study is in the form of a description test in the form of pre-test and post-test and data analysis is carried out with the Independent Sample t test. The results of the test calculation t were obtained by score signifikan 0,000 < 0,05. The results of the effectiveness questionnaire with an average value of the experimental class of 3.68, the control class of 3.57 and the percentage of the experimental class of 73,63%, the control class of 71.37%. Therefore it can be concluded that: 1) There is an Effect of the Effect of the Problem Based Learning Model Assisted by the Desmos Application on the Ability of Mathematical Literacy of MAS Al Washliyah Students 12 Perbaungan; 2) The Effectiveness of the Use of the Desmos Application in the quadratic function material on the Mathematical Literacy Ability of MAS Al Washliyah 12 Perbaungan.